166. Bring your boots: wading through GI PCR panel diagnostic stewardship applications. (15th December 2022) - Bennett, Nicholas; Boyd, Sarah E; Sattler, Jeffrey; Boos, Ginny; Johnston, Cara; Humphrey, Matt; Aragon, Laura; Aragon, Laura; Essmyer, Cynthia
Abstract: Background: Infectious diarrhea is a common cause of emergency department (ED) visits and hospital admissions. Polymerase chain reaction (PCR) testing allows for quick and expansive pathogen identification and facilitates earlier targeted treatment. We implemented a multiplex gastrointestinal (GI) PCR panel in 2014. In collaboration with the Antimicrobial and Diagnostic Advisement Program (ADAP), post-launch optimization strategies have changed test use. We evaluate the impact of diagnostic stewardship initiatives. Methods: GI PCR testing was initially unrestricted for ED or inpatients within 72 hours of admission. After fielding many questions regarding interpretation, the ADAP developed a guidance document in June 2019 regarding treatment considerations for all potential organisms detected. In January 2020, organism-specific treatment considerations were embedded in the test results real-time treatment guidance (figure 1). A pre-post quality improvement assessment of the changes was performed. In August 2021, individual GI PCR panel orders were replaced with an order set containing a decision tree to provide passive guidance evaluating acute vs chronic diarrhea, assessing recent antibiotic use (to consider C. difficile testing), no testing scenarios, and avoiding repeat testing (figure 2). Figure 1 Example of templated comments for Norovirus embedded within GI PCR panel results. Figure 2 GI PCR panel order set Results: GI PCR panel use peaked in 2019 with 3, 142 tests processed. The guidance document was less helpful, requiring an external site link. Embedding organism-specific GI PCR guidance significantly improved appropriate antibiotic prescribing (77.9 vs 89.1%, p=0.001). A precipitous drop off in GI PCR test orders occurred after the COVID-19 pandemic began (1, 774 in 2020), partly attributed to supply chain issues. When comparing intra-pandemic years (2020 vs 2021), implementation of a smart order set was associated with a 51.3% reduction in orders (1, 774 vs 864) and 131, 000 in savings despite significant patient volume increases in 2021. Low use rates have persisted into the first quarter of 2022 (n=229). Conclusion: Diagnostic stewardship changes should be proactive and contextually relevant at the time of result interpretation. Antimicrobial stewardship programs are uniquely positioned to lead optimization initiatives and drive clinical and cost-effective solutions. Disclosures: All Authors : No reported disclosures.